HUBUNGAN PENGGUNAAN GAME INTERAKTIF BERBASIS CANVA WEB TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PENJUMLAHAN SISWA KELAS II SD INPRES SAILONG - Rahmi Aulia; St. Aulia Bahar; Nur Padillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low mathematical problem-solving ability of students, especially in understanding the concept of addition at SD Inpres Sailong. The purpose of this study was to find out the relationship between the use of  interactive games based on Canva web and students' mathematical problem-solving skills. This quantitative research uses a correlational design with the subjects of grade II students. The data collection technique was carried out through a validated student perception questionnaire and a mathematical problem-solving ability test compiled based on the Polya indicator, including: understanding the problem, planning the solution, implementing the plan, and re-examining the results. Data analysis was carried out through the Product Moment correlation test  from Pearson's. The results showed that the correlation coefficient value r = 0.863 with a significance level of p < 0.001 which indicates a very strong and positive relationship, which means that the higher the quality of using  Canva-based interactive games, the higher the students' mathematical problem-solving skills. This study concludes that digital learning media is effective as a cognitive bridge to transform abstract mathematical concepts into concrete and fun learning experiences in rural areas.